Social Initiatives in Food Consumption and Distribution as Part of Sustainable Consumption and Sharing Economy - Katarzyna Bachnik; Justyna Szumniak-Samolej (Journal of Entrepreneurship, Management and Innovation)

(untitled)
The aim of this paper is to extract and describe recent social initatves in food consumpton and distributon in Poland and indicate their characteristcs related to sustainable consumpton, sharing economy and collaboratve consumpton and to indicate the processes, mechanisms and future development optons. Food is among areas that seem to adapt to those ideas more easily which means that individual consumers seem to see value in behaving in a more responsible way. In Poland, social awareness is rather limited and responsible behavior happens on a minor scale for the moment, but more internatonal research shows the great potental of sharing economy. Food is being wasted therefore it consttutes a good ground for changing consumpton habits. The paper presents four chosen social initatves in Poland that refer to a sustainable consumpton philosophy and collaboratve consumpton. Those mini case studies are backed by a thorough analysis of relevant literature, theme contents on websites, and results of secondary research studies dedicated to the issues discussed in the paper. Due to the qualitatve character of the study, it shall be followed by more quanttatve research to allow for more general insights and conclusions.